COMPARISON OF PHYSICAL CHEMICAL CHARACTERISTICS OF SOIL ON LANDS WITH DIFFERENT REVEGETATION AGES AT THE KELUBIR SITE OF PT PESONA KHATULISTIWA NUSANTARA, BULUNGAN, NORTH KALIMANTAN - Muwaffaq, Farih
This research was conducted at the Kelubir Site of PT Pesona Khatulistiwa Nusantara, Bulungan, North Kalimantan, with the objective to compare the physical and chemical characteristics of the soil in areas with different revegetation ages. Post-mining lands often exhibit significant changes in the physical and chemical characteristics of the soil, which can affect the revegetation process and ecosystem recovery. In this study, soil samples were taken from lands that had undergone the revegetation process over various periods, ranging from those that had just begun the process in 2020 to those that had been undergoing the process for 10 years since 2013. The parameters tested include pH, Organic-C, Total-N, C/N Ratio, P2O5 (Bray), K2O HCl 25%, Basic Cations (K-dd, Na-dd, Ca-dd, Mg-dd), Cation Exchange Capacity (CEC), Base Saturation, and Pb. The laboratory test results showed variations in the physical and chemical characteristics of the soil between the revegetated areas and the natural forest. The pH value of the soil in all revegetated and natural forest areas ranged from 4.93 to 5.16, indicating that the soil has acidic properties. The Pb content in all revegetated and natural forest areas was in the range of 4.385 ppm to 23.55 ppm. These conditions indicate that revegetation gives an indication of changes to the physical and chemical characteristics of the soil in post-mining lands. The physical and chemical properties of the soil in lands with different revegetation ages underwent significant changes. There was an increase in organic carbon and nitrogen content with increasing revegetation age. This shows the accumulation of organic material and improved nutrient availability, necessitating further efforts to improve soil quality on revegetated lands. Thus, this study makes a significant contribution to understanding how the revegetation process affects the physical and chemical characteristics of the soil in post-mining lands, and the results can be used to design more effective revegetation strategies in the future.